Profil Pedagogical Content Knowledge (PCK) Guru Sekolah Dasar pada Konteks Masalah Pecahan - Amri, Mira Amelia; Yurniwati; Dulyapit, Apit; yunus, mahmud (Jurnal PEKA (Pendidikan Matematika), 2026)
ABSTRACT: This study aims to describe the Pedagogical Content Knowledge (PCK) profile of five elementary school teachers (Master’s students in Primary Education with teaching experience, $N=5$) in analyzing contextual fraction numeracy problems. Employing a descriptive qualitative approach supported by illustrative quantitative analysis (collective case study), data were collected through case-based instruments (Vignette, CoRe, and PaP-eRs) and in-depth interviews. The findings indicate that the teachers' PCK is at a developing level (adequate), characterized by incomplete integration across dimensions. Specifically, Content Knowledge (CK) was strong in procedural aspects but weak in conceptual understanding. Knowledge of Students (KoS) could identify student errors, but the analysis of misconceptions' roots (diagnostic) remained descriptive. Instructional Strategies (KoIS) showed an initial use of visual contexts but lacked systematic planning for the transition from concrete to abstract. Knowledge of Curriculum (KoC) was the weakest aspect, with understanding tending to be administrative rather than integrative across numeracy topics. This study concludes that strengthening the teachers' PCK should focus on developing conceptual reflection and integrating PCK dimensions through case-based practices. Given the nature of this small case study, the results are not generalizable. ABSTRAK: Penelitian ini bertujuan mendeskripsikan profil Pedagogical Content Knowledge (PCK) lima guru sekolah dasar (mahasiswa S2 Pendidikan Dasar dengan pengalaman mengajar, N=5) dalam menganalisis masalah numerasi pecahan kontekstual. Menggunakan pendekatan kualitatif deskriptif dengan dukungan kuantitatif ilustratif (studi kasus kolektif), data dikumpulkan melalui instrumen berbasis kasus (Vignette, CoRe, dan PaP-eRs) dan wawancara mendalam. Hasil penelitian menunjukkan bahwa PCK guru berada pada tingkat berkembang (cukup), ditandai oleh ketidakutuhan integrasi antar-dimensi. Secara rinci, Content Knowledge (CK) kuat pada aspek prosedural tetapi lemah pada pemahaman konseptual. Knowledge of Students (KoS) mampu mengidentifikasi kesalahan siswa, tetapi analisis akar miskonsepsi (diagnostik) masih bersifat deskriptif. Instructional Strategies (KoIS) mulai menggunakan konteks visual, namun belum sistematis dalam merancang transisi dari konkret ke abstrak. Knowledge of Curriculum (KoC) merupakan aspek terlemah, dengan pemahaman yang cenderung administratif dan belum integratif lintas topik numerasi. Penelitian ini menyimpulkan bahwa penguatan PCK guru perlu diarahkan pada pengembangan refleksi konseptual dan integrasi dimensi PCK melalui praktik berbasis kasus. Mengingat sifat studi kasus kecil ini, hasilnya tidak dapat digeneralisasi